The Role of Parents at Mathematics Learning Innovation in Early Education - Rahmawati, Miftah Sigit; Amri, Irman (Indonesian Journal of Early Childhood Education Studies, 2020)
In digital era, it is possible for the term "home education" which presents the role of the family to the childhood education. The development of children's mathematics involved role of parents lies, so a mechanism needs to be established about the importance of mathematics learning in the early years and its forms about mathematical activities for children. Learning mathematics in early childhood connects the use of formative values, namely observation, assignments, and interviews for planned teaching. Pedagogical practice focuses on the involvement of children in games, reading stories/picture books, doing project work, and learning mathematics through art or physics. This gives the explanation that children in early education with their settings involve mathematical ideas. This research aims to provide solutions and ideas for parents in teaching children of early age (0-3) years old on mathematics. This research also provides an explanation of parental involvement in teaching mathematics by playing together and preparing children to face mathematics at the next level. The research method used is based on field research, literature studies, and observations. Report of evaluation and observation provide good results with the use of one of the learning methods, namely the montessori method. It also gives an explanation of the importance of togetherness of children and parents in learning mathematics without eliminating children's play time.